LoLiPEM: Long life proton exchange membrane fuel cells. (21st January 2016) - Barbieri, G.; Brunetti, A.; Di Vona, M.L.; Sgreccia, E.; Knauth, P.; Hou, H.Y.; Hempelmann, R.; Arena, F.; Beretta, L.D.; Bauer, B.; Schuster, M.; Ossó, J.O.; et al.
Abstract: This paper presents the main results obtained during the European project (FCH-JU) "LoLiPEM – Long-life PEM-FCH & CHP systems". The paper describes significant improvements in the polymer electrolyte by tailored heat treatments for cross-linking of Sulfonated Poly(ether ether ketone) (SPEEK), obtained without any addition of cross-linker species. The reported properties of the ionomers include mechanical properties, gas permeability and ionic conductivity. Innovative gas-diffusion electrodes are fabricated by the electrochemical deposition of Pt catalyst; the fuel cell current–voltage characteristics are reported with Nafion and SPEEK-based binder. The fuel cell performances at 80 °C of membrane-electrode-assemblies containing a SPEEK membrane with a cross-linking degree of 32% are among the best in the literature compared with the PEMFC using membrane alternative than Nafion. Highlights: Polymer exchange membrane fuel cells characterized above 100 °C. Polymer electrolyte by tailored heat treatments for cross-linking. Cross-linked sulfonated polyetheretherketone. Innovative gas-diffusion electrodes by electrochemical deposition of Pt catalyst. Membrane tensile strength.